A REVIEW ON MOTHER GODDESS PARADOX IN LYDIAN SYNCRETISM - Külahlı, Nuriye (Fırat University, 2024)
The cultural mosaic of the Lydian civilization manifests itself most intensely in its religious structure. Many gods and goddesses attract attention in Lydian syncretism. While goddesses stand out with their different characteristics, the problem of the mother goddess has long been a subject of curiosity for today's researchers. This situation has the nature of a paradox as there is no consensus on this situation with different opinions. Lydian goddesses of Anatolian and Greek origin stood out with their different characteristics and spheres of influence. However, which one is the mother goddess remains a mystery. Artemis, Demeter, Kore, Kybele and Athena are the goddesses most frequently mentioned in ancient sources and most frequently depicted in visual finds. In this case, the Greek goddesses, who are numerous in number, and the famous Anatolian goddess Kybele, whose sphere of influence is quite wide and in a powerful position, face each other in the same pantheon. In this study, an evaluation was made by considering the influence areas of Lydian goddesses and their frequency of reflection in existing epigraphic and numismatic finds. In this evaluation of the mother goddess paradox in Lydian syncretism, ancient artifacts, Sardis inscriptions and coins were mainly examined.

Lidya uygarlığının kültürel mozaiği, en yoğun şekilde dini yapısında kendini göstermektedir. Lidya senkretizmi içinde oldukça fazla tanrı ve tanrıça dikkatleri çekmektedir. Tanrıçalar farklı özellikleri ile öne çıkarken ana tanrıça sorunu uzun zamandır günümüz araştırmacılarının merak konusu olmuştur. Farklı görüşlere sahip olan bu durum üzerine bir fikir birliği sağlanamadığından bir paradoks niteliği taşımaktadır. Anadolu ve Yunan kökenli olan Lidya tanrıçaları, farklı özellikleri ve etki alanları ile öne çıkmışlardır. Ancak hangisinin ana tanrıça olduğu konusun gizemini korumaktadır. Artemis, Demeter, Kore, Kybele ve Athena antik kaynaklarda en çok isimleri geçen ve görsel buluntularda en sıklıkla tasvir edilen tanrıçalardır. Bu durumda sayıca fazla olan Yunan tanrıçalarının varlığı ve etki alanı oldukça geniş olan ve güçlü konumdaki ünlü Anadolu tanrıçası Kybele aynı panteonda karşı karşıyadır. Bu çalışmada, Lidya tanrıçalarının etki alanları ve mevcut epigrafik ve numizmatik buluntulara yansıma sıklıkları ele alınarak değerlendirme yapılmıştır. Lidya senkretizmindeki ana tanrıça paradoksu üzerine yapılan bu değerlendirmede antik eserler, Sardis yazıtları ve sikkeleri ağırlıklı olarak incelenmiştir.
Lidya Senkretizminde Ana Tanrıça Paradoksu Üzerine Bir Değerlendirme
Keywords: Literary Studies (Other); Edebi Çalışmalar (Diğer); Asian Cultural Studies; Asya Kültürü Çalışmaları; Multicultural; Intercultural and Cross-Cultural Studies; Çok Kültürlü ve Kültürlerarası Çalışmalar